2021
DOI: 10.1111/jcmm.16669
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐132 down‐regulates high glucose‐induced β‐dystroglycan degradation through Matrix Metalloproteinases‐9 up‐regulation in primary neurons

Abstract: Cognitive dysfunction is one of the complications of diabetes. Unfortunately, there is no effective methods to block its progression currently. One of the pathophysiological mechanisms is synaptic protein damage and neuronal signal disruption because of glucose metabolism disorder. Dystroglycan protein, located in the post‐synaptic membrane of neurons, links the intracellular cytoskeleton with extracellular matrix. Abnormal expression of dystroglycan protein affects neuronal biological functions and leads to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Abnormal expression of vascular endothelial growth factor (VEGF) and insulin resistance in DM patients may also account for the damage of WM as well as the decreased volume of CBF in the hippocampus, occipital lobe, and default model network related areas (146)(147)(148)(149). In addition, pathological cerebrovascular neovascularization, increased blood-brain barrier (BBB) permeability, cerebrovascular pericyte dysfunction, and synaptic protein injury may be responsible for the ability of hyperglycemia to affect cognition (150)(151)(152).…”
Section: Effects Of Comorbidities On Cognitive Function In Patients W...mentioning
confidence: 99%
“…Abnormal expression of vascular endothelial growth factor (VEGF) and insulin resistance in DM patients may also account for the damage of WM as well as the decreased volume of CBF in the hippocampus, occipital lobe, and default model network related areas (146)(147)(148)(149). In addition, pathological cerebrovascular neovascularization, increased blood-brain barrier (BBB) permeability, cerebrovascular pericyte dysfunction, and synaptic protein injury may be responsible for the ability of hyperglycemia to affect cognition (150)(151)(152).…”
Section: Effects Of Comorbidities On Cognitive Function In Patients W...mentioning
confidence: 99%
“…Furthermore, a negative relationship was observed between concentration of fasting glucose and miR-132 levels in GDM patients. High blood sugar exacerbated MMP-9 expression by suppressing miR-132 levels ( Dou et al, 2021 ). In contrast, ( Florijn et al, 2020 ) found that increased miR-132 circulating levels were related to T2D with nephropathy, and that focusing it reduced blood sugar and enhanced insulin production.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were subjected to the Morris water maze test in order to measure their spatial learning and memory functions as previously described. 20 In brief, the animals underwent four consecutive trials each day over a 5-day memory acquisition trial (training). Subsequently, the mice were trained to swim four times/day in order to find the hidden platform.…”
Section: Mwm Testmentioning
confidence: 99%